2006
DOI: 10.1037/0735-7028.37.2.183
|View full text |Cite
|
Sign up to set email alerts
|

The need for continuing education in ethics as reported by rural and urban mental health care providers.

Abstract: Continuing professional education (CPE) sponsors planning events for mental health care licensees can assure better attendance if they can successfully address the needs of their target audience. Offering topics of interest is particularly crucial when CPE events need to draw large numbers of attendees to be financially viable. A survey of nearly 400 health licensees regarding CPE needs, especially as related to ethics, revealed that the greatest interest in such CPE was reported by master's-level mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Some states mandate professional ethics credits. Research reinforces the importance of this kind of training (M. E. Johnson, Brems, Warner, & Roberts, ). Experienced counselors place a strong emphasis on the development of the counseling relationship and how this enhances their ability to ethically provide counseling (Jennings, Sovereign, Bottorff, Mussell, & Vye, ).…”
Section: Implications and Recommendationssupporting
confidence: 53%
“…Some states mandate professional ethics credits. Research reinforces the importance of this kind of training (M. E. Johnson, Brems, Warner, & Roberts, ). Experienced counselors place a strong emphasis on the development of the counseling relationship and how this enhances their ability to ethically provide counseling (Jennings, Sovereign, Bottorff, Mussell, & Vye, ).…”
Section: Implications and Recommendationssupporting
confidence: 53%
“…Although there has been increased focus on PPC among counselors‐in‐training (Brear & Dorrian, ; Brown‐Rice & Furr, ; Gaubatz & Vera, ; Kress & Protivnak, ; Ziomek‐Daigle & Christensen, ), along with practitioner‐focused research (Johnson, Brems, Warner, & Roberts, ; Pooler, Sheheen, & Davidson, ), there is a lack of emphasis on professional expectations for counselor educators. There has been some focus on specific aspects of PPC across disciplines, including cognitive decline (Clemens, Horwitz, & Sharp, ), sexual intimacies in graduate training (Kress & Dixon, 2007; Zakrzewski, ), depression and suicide (Kleespies et al, ), abuse of alcohol and other drugs (Pooler et al, ; Seibert, ), dual relationships (Boland‐Prom, ; Nigro, ), and vicarious traumatization (Baird & Kracen, ).…”
Section: Competency Issues Among Professionalsmentioning
confidence: 99%
“…While limited research has confirmed the challenges of delivering substance abuse treatment in rural contexts, further research focusing on rural substance abuse treatment providers using a detail-rich qualitative approach is needed to understand the unique challenges of working in rural contexts (Chipp et al, 2011; Johnson, Brems, Warner, & Roberts, 2006). …”
Section: Introductionmentioning
confidence: 99%